All‐Polymer Solar Cells: Recent Progress, Challenges, and Prospects - Wang, Gang; Melkonyan, Ferdinand S.; Facchetti, Antonio; Marks, Tobin J. (Angewandte Chemie (International ed.), 2019)
For over two decades bulk‐heterojunction polymer solar cell (BHJ‐PSC) research was dominated by donor:acceptor BHJ blends based on polymer donors and fullerene molecular acceptors. This situation has changed recently, with non‐fullerene PSCs developing very rapidly. The power conversion efficiencies of non‐fullerene PSCs have now reached over 15 %, which is far above the most efficient fullerene‐based PSCs. Among the various non‐fullerene PSCs, all‐polymer solar cells (APSCs) based on polymer donor‐polymer acceptor BHJs have attracted growing attention, due to the following attractions: 1) large and tunable light absorption of the polymer donor/polymer acceptor pair; 2) robustness of the BHJ film morphology; 3) compatibility with large scale/large area manufacturing; 4) long‐term stability of the cell to external environmental and mechanical stresses. This Minireview highlights the opportunities offered by APSCs, selected polymer families suitable for these devices with optimization to enhance the performance further, and discusses the challenges facing APSC development for commercial applications. APSCs offer all: All‐polymer solar cells have attracted great attention, owing to rational design, improved morphology, strong absorption, enhanced stability etc. This Minireview highlights the opportunities of APSCs, selected polymer families suitable for these devices with optimization to enhance the performance further, and discusses the challenges facing APSC development for commercial applications.